“The Flow in the Funnel”: Modeling Organizational and Individual Decision-Making for Designing Financial AI-Based Systems - Talamo, Alessandra; Marocco, Silvia; Tricol, Chiara (Frontiers in Psychology, 2021)
Nowadays, the current application of Artificial Intelligence (AI) to financial context is opening to a new field of study, named financial intelligence, in which the implementation of AI-based solutions as “financial brain” aims at assisting in complex decision-making (DM) processes as wealth and risk management, financial security, financial consulting, and blockchain. For Venture Capitalists Organizations (VCO), this aspect becomes even more critical since different actors (shareholders, bondholders, management, suppliers, customers) with different DM behaviors, are involved. One last layer of complexity is the potential variation of behaviors performed by managers even in presence of fixed organizational goals. The aim of the paper is twofold: a general analysis of the debate on implementing AI in DM processes is introduced, and a proposal for modeling financial AI-based services is presented. A set of qualitative methods based on the application of cultural psychology is presented for modeling financial DM processes of all actors involved in the process, machines as well as individuals and organizations. The integration of some Design Thinking techniques with Strategic Organizational Counseling supports the modeling of a hierarchy of fund-seekers’ selective criteria and the creation of an innovative value proposition accordingly with VCOs’ goals to be represented and supported in AI-based systems. Implications suggest that human/AI integration in the field can be implemented by developing systems where AI can be conceived in two distinct functions: a) automation: treating Big Data from the market defined by VCO’s management; b) support: creating alert systems which coherently with VCO’s ordered weighted decisional criteria.